PENYULUHAN PENCEGAHAN BAHAYA BAKTERI SALMONELLA Sp. SEBAGAI PENCETUS INFEKSI DEMAM TIFOID ATAU TIFUS - Eka Mutiara Hikmah (Pusat Riset dan Inovasi Nasional, 2021)
Typhoid fever or typhus can be caused by the bacteria Salmonella Sp. contained in eggs. Handling eggs properly can avoid the risk of typhoid fever. People who have a weakened immune system are particularly at risk of developing typhoid fever. This service is aimed at the community, especially housewives who often consume eggs in the form of counseling and distributing online questionnaires about the dangers of Salmonella sp. which can infect humans if the handling and processing is not good. Counseling is carried out online through zoom meetings with 33.33% housewives, 57.15% working people, and 9.52% students. After the counseling was carried out, the authors evaluated the knowledge of the extension participants before the presentation of the material and after the presentation of the material. The results obtained are participants can increase their knowledge with a percentage of 80.96% having answered correctly the questions given.